2022
DOI: 10.1021/acs.langmuir.2c01556
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly Zr-Based MOF for Pesticide Delivery: Ultrahigh Loading Capacity, pH-Responsive Release, Improved Leaf Affinity, and Enhanced Antipest Activity

Abstract: The stimuli responsive pesticide delivery system (PDS) has drawn increasing attention in recent years, a system which can effectively improve the utilization of pesticides. In the current research, we report a pH responsive PDS by using carboxymethyl cellulose (CMC) modified Zr-based metal organic frameworks (UiO-66-NH2) as the nanocarrier for acetamiprid (ATP). UiO-66-NH2-CMC possesses a large surface area and abundant pores, which can effectively load ATP, and the loading rate is as high as 90.79%. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Enhancing the adhesion of pesticides on foliage can effectively improve pesticide utilization. Based on the potential adhesion and prominent viscoelasticity of JNSs-stabilized Pickering emulsions presented in rheological measurement, an adhesive pesticide emulsion is prepared by loading the model pesticide Av (termed Av-Emul). Along the route reported in our previous work, the adhesion ability of the Av-Emul is evaluated by comparing the amounts of samples remaining on interfaces before and after simulating rainwash.…”
Section: Resultsmentioning
confidence: 99%
“…Enhancing the adhesion of pesticides on foliage can effectively improve pesticide utilization. Based on the potential adhesion and prominent viscoelasticity of JNSs-stabilized Pickering emulsions presented in rheological measurement, an adhesive pesticide emulsion is prepared by loading the model pesticide Av (termed Av-Emul). Along the route reported in our previous work, the adhesion ability of the Av-Emul is evaluated by comparing the amounts of samples remaining on interfaces before and after simulating rainwash.…”
Section: Resultsmentioning
confidence: 99%
“…In 2022, a pH-responsive Zr-based MOF was constructed by Shen and co-workers to enhance the utilization of pesticides and insecticidal activity in pest management . Carboxymethyl cellulose (CMC), a pH-responsive polymer molecule, was modified on the surface of UiO-66-NH 2 by an amidation reaction, followed by the introduction of acetamiprid (ATP) in the pores of UiO-66-NH 2 –CMC through physical adsorption to achieve ATP@UiO-66-NH 2 –CMC with an ultrahigh loading content of 90.79%.…”
Section: Mof-based Nanoplatforms For Crop Protectionmentioning
confidence: 99%
“…In 2022, a pH-responsive Zr-based MOF was constructed by Shen and co-workers to enhance the utilization of pesticides and insecticidal activity in pest management. 119 Carboxymethyl cellulose (CMC), a pH-responsive polymer molecule, was modified on the surface of UiO-66-NH 2 by an amidation For another instance, Shen, Wu, Song, and co-workers developed a temperature-responsive nanocomposite, namely, IDC@UiO-66-(COOH) 2 -PNIPAm, to release pesticide and efficiently control Spodoptera f rugiperda. 120 UiO-66-(COOH) 2 composed of Zr 4+ and pyromellitic acid (H 4 BTEC) linkers was used as a reservoir to load insoluble indoxacarb (IDC), a broad-spectrum insecticide, with a high loading capacity of 78.69%, followed by the modification of a temperaturesensitive poly(N-isopropylacrylamide) (PNIPAm) by a co-valent grafting approach to develop IDC@UiO-66-(COOH) 2 -PNIPAm.…”
Section: Journal Of Agricultural Andmentioning
confidence: 99%
“…Overall, we had evaluated the comprehensive performance of our FPP with commercial formulations as controls, as summarized in Table S3. Considering the field applicability of these formulations, 44 we found that (1) rapid-dissolving FPP could be directly applied in powder form, resulting in a nanodispersion without the "coffee ring effect" and storage stability issues; (2) FPP possessed better foliar adhesion, wettability, and antibouncing ability than other SCs, effectively improving the deposition of fipronil; and (3) smart FPP with unique precise delivery also exerted an unimpaired short-term efficacy compared with commercial SCs. In conclusion, our FPP with nanodispersion, full wetting, and precise delivery showed significant advantages in controlling the entire journey of hydrophobic pesticide application compared with other SCs, without organic solvents, surfactants, and materials.…”
Section: Comprehensive Field Applicability Comparison Between Fpp And...mentioning
confidence: 99%